Microwave assisted sinter molding of polyetherimide/carbon nanotubes composites with segregated structure for high-performance EMI shielding applications. (29th September 2019) - Feng, Dong; Wang, Qingqing; Xu, Dawei; Liu, Pengju
Abstract: The formation of segregated conductive structure in a polymer matrix can remarkably improve the electrical and EMI shielding performance. Nevertheless, the insufficient interfacial bonding force among polymer domains generated during the conventional hot compressing process will seriously deteriorate the mechanical property of the final composite. Herein, high-performance polyetherimide/carbon nanotubes (PEI/CNTs) composites with segregated structure were facilely fabricated for EMI shielding applications using CNTs as both solder and a conductive framework. The surface-localized CNTs were selectively and vigorously heated upon exposure to microwave (MW) irradiation, with an appropriate pressure stress applied subsequently, ensuring enhanced local polymer mobility and entanglement across the interfacial regions. Consequently, an excellent conductivity and EMI shielding effectiveness (EMI SE) of 17.98 S/m and 34.6 dB, respectively, at 8.2–12.4 GHz were achieved in the PEI/CNTs composites only employing 4.0 wt% CNTs, along with the tensile strength of 36 MPa, due to the superb welding induced by the MW selective sintering. All the results indicated that this effort provided a novel, economical and easily industrialized concept for fabricating segregated high-performance polymer composites for EMI shielding applications. Graphical abstract: Image 1